Kenya : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
The Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper Progress Report on Kenya reviews poverty reduction strategy. The Investment Program for the Economic Recovery Strategy for Wealth and Employment Creation (IP-ERS) that the government of Kenya has recently submitted to the IMF and World Bank is Kenya's poverty reduction strategy paper. The poverty diagnosis in the IP-ERS document is based on very limited information. The IMF staff welcomes the government's plans to undertake needed financial sector reforms to mobilize funds for investment, improve fiscal management, and strengthen governance.